PERBANDINGAN SISTEM DIRECT-ADMINESTERED MUNICIPALITY DI TIONGKOK DAN SISTEM DESENTRALISASI DI INDONESIA TERHADAP PELAKSANAAN OTONOMI DAERAH DI INDONESIA - NIM. A1011211121, YOGA PRATAMA (Jurnal Fatwa Hukum, 2025)
Abstract This research discusses the comparison between the direct-administered municipality system in China and the decentralization system in Indonesia in relation to the implementation of regional autonomy. The purpose of this study is to understand the characteristics of local governance systems in both countries, analyze the relevance and implications of the direct-administered municipality model if conceptually applied in Indonesia, and assess its impact on governance, legal, and political structures. The research employs a normative legal method using a comparative law approach. Data were obtained through literature studies on legislation, official documents, and academic sources related to local government systems in Indonesia and China. The results of the study show that China adopts a highly centralized unitary state system in which four major cities Beijing, Shanghai, Tianjin, and Chongqing have the status of direct-administered municipalities and are placed directly under the authority of the central government. Meanwhile, Indonesia implements broad decentralization through the delegation of authority to provinces, regencies, and cities based on the 1945 Constitution of the Republic of Indonesia and Law No. 23 of 2014 on Regional Government. Conceptually, the adoption of a direct-administered municipality system in Indonesia could enhance bureaucratic efficiency and accelerate development in strategic national areas such as Jakarta or the new capital city, Nusantara. However, constitutionally and politically, such a system may reduce regional autonomy, weaken public participation, and potentially create interregional inequality. Therefore, its implementation should be limited and regulated strictly by law to ensure alignment with the democratic and decentralized principles that characterize Indonesia’s regional government system. Keywords: Direct-Administered Municipality; Decentralization; Regional Autonomy; China; Indonesia. Abstrak Penelitian ini membahas perbandingan antara sistem direct-administered municipality di Tiongkok dengan sistem desentralisasi di Indonesia terhadap pelaksanaan otonomi daerah. Tujuan penelitian ini adalah untuk memahami karakteristik sistem pemerintahan daerah di kedua negara, menganalisis relevansi dan implikasi sistem direct-administered municipality jika diterapkan di Indonesia, serta menilai dampaknya terhadap tata kelola pemerintahan, hukum, dan politik nasional. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan komparatif hukum. Data diperoleh melalui studi pustaka terhadap peraturan perundang-undangan, dokumen resmi, dan literatur akademik terkait sistem pemerintahan daerah di Indonesia dan Tiongkok. Hasil penelitian menunjukkan bahwa Tiongkok menganut sistem negara kesatuan yang bersifat sangat sentralistik, di mana empat kota utama (Beijing, Shanghai, Tianjin, dan Chongqing) berstatus direct-administered municipality dan berada langsung di bawah kendali pemerintah pusat. Sedangkan Indonesia menerapkan desentralisasi luas melalui pelimpahan kewenangan kepada provinsi, kabupaten, dan kota berdasarkan UUD NRI Tahun 1945 dan UU No. 23 Tahun 2014. Secara konseptual, penerapan sistem direct-administered municipality di Indonesia dapat meningkatkan efektivitas birokrasi dan efisiensi pembangunan di wilayah strategis nasional seperti Jakarta atau Ibu Kota Nusantara. Namun, secara konstitusional dan politis, sistem tersebut dapat mengurangi otonomi daerah, melemahkan partisipasi publik, dan berpotensi menimbulkan ketimpangan antardaerah. Oleh karena itu, penerapan model tersebut hanya dapat dilakukan secara terbatas dengan pengaturan hukum yang ketat, agar tetap sejalan dengan prinsip demokrasi dan desentralisasi yang menjadi ciri khas pemerintahan daerah di Indonesia. Kata Kunci: Direct-Administered Municipality; Desentralisasi; Otonomi Daerah; Tiongkok; Indonesia.